The infotainment report: evolution of the genre in the general-interest television channels in Spain (1990-2020) - García-Avilés, José Alberto (2021)
The macro-genre of TV infotainment comprises several genres and, regardless of the label under which each is defined, offers a wide range of variations and combinations that are constantly being reinvented. The infotainment report implies a mutation of the purely informative genre, as the representation of everyday lives has become a major television spectacle with its own characteristics. This research identifies 29 infotainment programmes broadcast on generalist television in Spain between 1990 and 2020 and analizes their evolution. The channels that have broadcast the highest number of infotainment reports are La Sexta (eleven programmes) and Cuatro (eight), followed by TVE ‘s La 1 (four), Antena 3 (three) and Telecinco (three). The results show that infotainment reports, most of which are produced by companies outside the channels, have a documentary-style aesthetic, deal with stories about ordinary people, give the reporter a leading role, appeal to emotion and promote the hybridisation of the genre.